EMPOWERING RED RICE FARMERS THROUGH HOLISTIC ASSISTANCE IN ARALLE, MAMASA REGENCY, TOWARDS SOCIAL AND ECONOMIC INDEPENDENCE - Azizi, Muhammad; Zainuddin, Muhlis; Asri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Aralle Village, located in Aralle District, Mamasa Regency, is a highland area with an altitude of between 800 and 1,200 meters above sea level. This area has a cool climate with high rainfall that is very supportive of the cultivation of food crops, especially local rice such as red rice. This commodity has a distinctive taste and high nutritional value, so it has great potential to be developed as a superior local product. Unfortunately, this potential has not been fully utilized by the community, the majority of whom still practice traditional and subsistence farming. Limited access to infrastructure, particularly road conditions and agricultural product transportation, is a barrier to comprehensive agricultural development, from upstream to downstream. According to information from farmers around Aralle, the management of farmer groups does not pay attention to institutional aspects, marketing management aspects, and production aspects related to red rice, from planting to harvesting and post-harvest.